THE UNIQUENESS OF MODERN THEATER - Saparov Rinat Kuralbayevich (Scholar Express Journal, 2023)
Undoubtedly, one of the characteristic features of modern theater is its topicality, democracy and acute social orientation. Theater in most cases today has ceased to be an art for the intellectual elite - it began to express itself in the language of the masses, raising and experiencing the complex problems of our time
Keywords: Theatre; spectator; innovations